LOAD BALANCING METHOD IN THE CORE NETWORK OF MOBILE OPERATORS - Одарченко, Р. С.; Абакумова, А. О. (Science-based technologies, 2016)
The paper analyzes resource reservation algorithms and methods of traffic flows redistribution in the backbone mobile operator network. In these algorithms information is used about channels capacity and reliability that allows to increase the intensity of network segments, and thus the effective network capacity in general. Since requirements of data transfer for each service in network are different, so it should be used its network resource reservation algorithm for each service. Network traffic model was taken for consideration based on queuing system M/M/1-model. In the work, queuing system is considered as a prototype system for unloading the mobile operator core network. By using this system network load was investigated, and method of load balancing was developed in LTE transport network. The main differences between this method and most existing one is that it is dynamic, and allows to distribute load depending on the channel conditions between alternative routes with different value. As a result, the developed load balancing method in the mobile operator core network allows to achieve more balanced traffic distribution across the network and therefore higher performance.